Evaluating the Contribution of Women in the Field of Journalism - Rashmi Pandey; Pulkit Sharma (Recent Trends in Social Studies, 2025)
The role of women in journalism has evolved significantly over the years, with their contributions shaping the narratives, perspectives, and dynamics within the industry. This research paper aims to evaluate the multifaceted contributions of women in journalism, analyzing their impact on reporting, societal perceptions, and the advancement of gender equality within newsrooms. Through a comprehensive review of existing literature and case studies, this paper highlights the challenges faced by women in journalism, their achievements, and the broader implications of their presence in the field. Despite a major evolution in the role of women in journalism over time, their contributions are still frequently disregarded and underfunded. This research article seeks to evaluate the impact and significance of women in the field of journalism. Through a comprehensive analysis of historical context, current trends, challenges, and notable achievements, this study aims to shed light on the invaluable contributions of women journalists worldwide. By examining their roles in shaping public discourse, challenging societal norms, and advancing journalistic practices, this article advocates for greater recognition and support for women in journalism. The historical context of women in journalism is marked by a journey of perseverance, resilience, and trailblazing achievements amidst societal norms and systemic barriers. Throughout much of history, journalism was predominantly a male-dominated profession, with women facing significant challenges in entering and advancing within the field. However, despite these obstacles, women have played crucial roles in shaping the landscape of journalism and breaking new ground in various aspects of the industry.
Keywords: Women in journalism; contribution of female journalists; gender in media; impact of women in media; women’s role in journalism